Exploring the impact of meaning in life on the professional commitment of nursing students on the basis of general self-efficacy: a structural equation modelling approach - A. Panahi; S. Haghighi; N. Sayadi; M. Seyyedtabib (BMC Medical Education)
Abstract Background The professional commitment of nursing students ensures the retention rate of future nurses in the profession. The present study aimed to model the structural equations of the mediating effect of meaning in life on the relationship between general self-efficacy and the professional commitment of nursing students. Methods A cross-sectional correlational study was conducted, and a total of 407 nursing students from 6 nursing colleges in Khuzestan Province, who were randomly selected via a Proportional Stratified Sampling method, completed the General Self-Efficacy, Meaning in Life questionnaires and the Nursing Professional Commitment inventory anonymously. Descriptive and Pearson correlation analyses were performed with SPSS 23, and structural equation modelling was performed with AMOS 23.0. Results The results obtained from the structural equation model revealed that an increase in self-efficacy was associated with an increase in meaning in life (Beta=0.495, p<0.05). Additionally, with increasing meaning in life, nurses' professional commitment increased (beta=0.378, p<0.05). Given that the direct relationship between general self-efficacy and professional commitment to nursing was insignificant (p>0.05), meaning in life completely mediated these two variables. Conclusion Implementing interventions aimed at enhancing the sense of meaning in life and general self-efficacy among nursing students could increase their commitment to the nursing profession and thereby reduce the turnover rate of future nursing generations.